(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
This article deals with the peculiarities of the translation of non-finite forms of the verb from English into Russian in the belles-lettres. This problem is not elucidated well enough in linguistic and translation literature, while when translating non-finite forms into Russian one can face some difficulties. Sometimes while translating a text the accent falls on the lexical aspect, first of all on the shades of meaning, but syntactic mistakes sometimes invisible, lead not only to stylistic mistakes, but also the misrepresentation of the meaning. Non-finite forms can be used as a subject, a predicative, part of a compound verbal and modal predicate, an object, an adverbial modifier and an attribute. The infinitive has some nominal characteristics and can be used as a subject, part of a compound nominal predicate, an object and an attribute. As for its verbal characteristics it can take a direct object and has tense and voice distinguishes. As a subject, predicative and adverbial modifiers, it can be translated with the help of the infinitive or a noun. Complexes with the infinitive can be translated by subordinate clauses. If the infinitive is passive, the Russian subordinate clause should have either a passive construction or a non-finite form. If the infinitive is perfect the predicate in the Russian sentence should be used in the past tense. If the perfect infinitive has a passive form the predicative in the Russian subordinate clause should be used in the past tense and has passive voice or a non-finite form. Complex object can be translated by a subordinate clause, while complex subject can be translated only by a compound sentence. The gerund is such a non-finite form, which cannot be found in the Russian language. It can be translated into the Russian language with the help of the infinitive, a verbal noun or a subordinate clause. The combination of the gerund with a possessive pronoun or a noun in the possessive case form an equivalent of a subordinate clause. Russian present participles can be used only as an attribute, when used in the active voice, while English participles active can be used not only as an attribute, but also as an adverbial modifier. When translating a text, one should pay attention to the place of the participle in the sentence. If it is an attribute it is translated by a Russian participle, if it is used as an adverbial modifier, it is translated by a Russian adverbial participle in the imperative aspect. Participial constructions have no any equivalents in the Russian language, so they should be translated by an adverbial subordinate clause.